Paperless Mail Office System and Data Integration at UNIKA Soegijapranata - Albertus Dwiyoga Widiantoro (SISFORMA, 2018)
Paper-based correspondence has many constraints on sending, receiving, and filing. The filling makes it difficult to search document.  The purpose of this research is to facilitate the process of sending, searching, and integrating data and documents. With electronic-based office mail is expected to reduce paper usage. Application development methods using the SDLC method consist of system investigation, analysis, design environments, testing, training, and transition, operation and maintenance.Electronic-based office mail is able to solve many problems regarding the mail system such as speed of delivery, filing, and searching of documents. By utilizing the database system, documents can be stored well and integrated. It's cannot eliminate the use of paper. The main reason is the habit of employees needed paper evidence in their work